Multi-point shaking table test for long tunnels subjected to non-uniform seismic loadings - part II: Application to the HZM immersed tunnel. Issue 108 (May 2018) - Yu, Haitao; Yuan, Yong; Xu, Guoping; Su, Quanke; Yan, Xiao; Li, Chong
Abstract: A series of multi-point shaking table tests are conducted on a long immersed tunnel designed for the Hongkong-Zhuhai-Macau linkage (HMZ linkage) under non-uniform seismic excitations. Details of experimental setup are first presented with particular focuses on: shaking table array of the four independent shaking tables; dynamic similitude design between scale model of soil and tunnel structure and prototype model; design and fabrication of the scaled model tunnel and model soil; and procedure for simulation of non-uniform seismic waves. A series of testing cases of the shaking tables are carried out on the model tunnel using input motions with different seismic amplitudes. Dynamic responses measured from the experiment include acceleration of soil stratum and model tunnel, as well as extension and closure of immersion joints. Acceleration and deformation responses in the tunnel segments and their connecting joints are investigated and analyzed in the test cases under both uniform and non-uniform seismic loadings, and the capacity of critical structural components, such as extension of joints is evaluated. Results show that the non-uniform seismic excitation significantly aggravates the extension of immersion joints compared to the uniform excitation, and thus the non-uniform seismic effect should be considered in the design of immersed tunnels. Highlights: Multi-shaking-table tests are firstly conducted for the HZM immersed tunnel. Technical details of the test design and its implementation are fully addressed. Meaningful test data including extension of immersion joints are obtained. The non-uniform seismic input has a significant influence on the tunnel responses. Seismic performance of the immersed tunnel is evaluated based on the test data.